CONTRIBUTION TO THE STUDY OF SUCEAG POTTERY, CLUJ COUNTY, ROMANIA - BENEA, Marcel; LĂZĂRESCU, Vlad-Andrei; GOREA, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The site at Suceag, Cluj county, Romania, is composed of three different overlapping settlements, each having its own chronology: the first one is dated during the time of the Roman province of Dacia, the second one dated between the second half of the 4th century and the beginning of the 5th century AD and the last one broadly dated during the 7th-8th century AD. Because of this particular situation, our first attempt was to determine whether some direct connections between them truly existed. The petrographic analysis performed on a series of 56 samples coming from different types of pottery established after analysing all the ceramic material coming from the settlement at Suceag (cca. 4500 pottery fragments) showed that in this case we are only dealing with local products. The colour of the analysed potsherds vary from grey to black indicating reducing atmosphere (25 samples), from reddish-brown to yellowish-brown (24 samples) suggesting an oxidizing atmosphere during firing and 7 samples have a sandwich-type structure probably an incomplete thermal treatment. The matrix is relatively uniform, with clasts of various sizes (up to 3-4 mm). Macroscopically, quartz grains, micas, and ceramoclast could be observed. According to the microscopic grain size, two types of ceramics can be separated: semifine (lutitic-siltic-arenitic), and coarse (lutitic-arenitic-siltic). Based on the ratio between crystalline vs. amorphous phases, microcrystalline, and microcrystalline-amorphous fabrics were identified. As temper, crystalloclasts (quartz, micas, iron oxi-hydroxides, feldspars, amphibole, garnets, epidote, zircon), lithoclasts (quartzite, micaschist, gneiss, limestones), and ceramoclasts were identified. The observed bioclasts are represented by algae, and foraminifera remnants. The porosity consists of both primary, and secondary pores. The pore size vary from 0.5 x 1.5 mm to1.5 x 2.0 mm. Open porosity determined by water absorption capacity vary between 9.09 % - 23.10 %. The X-Ray diffraction analyses confirm the microscopic observations. According to the macroscopic aspects, microscopic features, and physical characteristics, the firing temperature of the studied ceramic fragments is estimated to be between 800-900°C.